Heterogeneous Trade Effects of Pre-Shipment Inspections - Cosimo Beverelli; Martin T. Braml; Lionel Gérard Fontagné; Alexander Keck; Gianluca Orefice (Center for Economic Studies and ifo Institute (CESifo), 2022)
Global imports subject to pre-shipment inspections (PSI) – a practice under which imports need to undergo a third party review process before shipment – shrank from 700 bn USD in 2010 to 87 bn in 2018. However, only little is known about the trade impact of such procedures, which on the one hand involve administrative costs, but on the other hand provide information. This paper – the first PSI analysis consistent with a structural gravity framework – shows that PSI requirements reduce bilateral trade and are most harmful for trade in differentiated manufacturing products. In contrast, PSI facilitate trade in food products. Trade in products subject to sanitary and phytosanitary measures even doubles when these measures are combined with PSI. Overall, counterfactual analysis suggests that the removal of PSI requirements between 2010 and 2018 implied a 2.6% increase in total imports across the 32 developing countries covered by our data.
Keywords: F13; F14; F17; 330; pre-shipment inspections; structural gravity; trade facilitation